Contradictory realities and competing perspectives: how discourses in education shape the teacher-self - Rose, Patrick Allen (Frontiers in Education, 2023)
This Foucauldian case study examines how dominant discourses in education operate to subtly constitute teachers as normalized subjects by producing knowledge and inducing techniques of power. The retellings of high school teachers are examined to demonstrate how they reconcile their own personal experiences and professional ethics with the static ideal images projected by competing political discourses. It is found in the localized context of a single American high school that public policy, technology, and teacher discourses represent teachers in certain ways and compel them to self-regulate themselves such that they internalize and reify imposed norms. However, teachers resist and alter these discourses to produce other possibilities for the critical teacher subject positions they actually occupy. A model is proposed to illustrate how different representations of the teacher-subject emerge from the collision, distribution, and legitimatization of these discourses. This study brings into view the ways teachers powerfully question and resist the constraints placed upon their conduct and draw on their personal relationships with each other to constitute their own professional identities.